2016
DOI: 10.1042/bsr20160134
|View full text |Cite
|
Sign up to set email alerts
|

G-1 exerts neuroprotective effects through G protein-coupled estrogen receptor 1 following spinal cord injury in mice

Abstract: Spinal cord injury (SCI) always occurs accidently and leads to motor dysfunction because of biochemical and pathological events. Estrogen has been shown to be neuroprotective against SCI through estrogen receptors (ERs), but the underlying mechanisms have not been fully elucidated. In the present study, we investigated the role of a newly found membrane ER, G protein-coupled estrogen receptor 1 (GPR30 or GPER1), and discussed the feasibility of a GPR30 agonist as an estrogen replacement. Forty adult female C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…GPR30 activation also induced the activation of PI3-kinase/Akt-dependent signaling and transactivation of the epidermal growth factor receptor via Src protein kinase [ 33 35 ]. Moreover, GPR30 increased Bcl-2 and BDNF by regulating the PI3K/Akt and MAPK/ERK signaling pathways [ 36 ]. Whether these second messenger signaling molecules are required for the GPR30-mediated downregulation of TLR4 in microglia needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…GPR30 activation also induced the activation of PI3-kinase/Akt-dependent signaling and transactivation of the epidermal growth factor receptor via Src protein kinase [ 33 35 ]. Moreover, GPR30 increased Bcl-2 and BDNF by regulating the PI3K/Akt and MAPK/ERK signaling pathways [ 36 ]. Whether these second messenger signaling molecules are required for the GPR30-mediated downregulation of TLR4 in microglia needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the crucial downstream proteins of PI3K/AKT are Bax and Bcl-2, which are related to apoptosis. Cheng et al found that promotion of AKT phosphorylation could increase Bcl-2 expression, thus decreasing the levels of Bax and cleaved caspase-3 in SCI 24. Moreover, PI3K/AKT pathway is also involved with autophagy 25.…”
Section: Discussionmentioning
confidence: 99%
“…The steroidal structure further confers anti-inflammatory and antioxidant properties, both reducing cellular toxicity and cell death (Chaovipoch et al, 2006; Cuzzocrea et al, 2008; Gupta and Hubscher, 2012; Jover-Mengual et al, 2010; Miller et al, 2005; Mosquera et al, 2014; Nilsen and Brinton, 2003; Ritz and Hausmann, 2008; Samantaray et al, 2011, 2016; Siriphorn et al, 2012; Sribnick et al, 2005, 2006, 2010; Yune et al, 2004, 2008; Zhao and Brinton, 2007). The GPER-1/GPR30 activation resulted in neuronal survival and better behavioral outcome after pathological conditions to the CNS, like SCI, traumatic brain injury and stroke (Cheng et al, 2016; Hu et al, 2012; Wang et al, 2017). The GPER-1 activation by G-1 (GPER-1 selective agonist) was shown to mediate a sexually dimorphic response after middle cerebral artery occlusion (MCAo) (Broughton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%